Shigella types encountered in shigellosis of children in Ankara - Akman, Muvaffak (The Turkish Journal of Pediatrics, 1961)
In the Hacettepe Children’s Hospital in Ankara, within the last three years, 108 strains of shigella were isolated from children between 0 and 14 years of age. Of these 81.48 per cent were Sh. flexneri, 12.96 per cent Sh. sonnei, 4.63 per cent Sh. dysenteriae and only one Sh. boydii. These results coincide well with the results published by other workers in Turkey, The most prevalent type of Sh. flexneri is Type 2b; out of 51 strains of Sh. flexneri, 35 (or 68.6 per cent) proved to be of this type. Berkman, who is the microbiologist of the United States Air Force Hospital in Ankara, informed us that the most prevalent type among 32 strains of shigella he isolated from American children was Sh. sonnei with Sh. flexneri occupying the second place in bacillary dysentery. The cause of this difference is not known. Most of the strains were isolated during the summer months. The chance of isolation increases after May and again decreases after September. There is no correlation between the isolations and the age groups of children as far as we could determine.